2018
DOI: 10.1017/s1368980018000861
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of ultra-processed food and obesity: cross sectional results from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) cohort (2008–2010)

Abstract: Results indicate the existence of associations between greater energy contribution from ultra-processed foods and higher BMI and WC, which are independent of total energy intake. These findings corroborate public policies designed to reduce the intake of this type of food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
101
0
25

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(143 citation statements)
references
References 37 publications
(67 reference statements)
17
101
0
25
Order By: Relevance
“…These foods present an unbalanced nutritional composition, lack micronutrients and phytochemicals, contain low levels of fiber and protein and are rich in free sugars, total fats, saturated and trans fats and sodium. 8 Previous studies have identified positive associations between consumption of ultra-processed foods and obesity, [9][10][11][12][13] metabolic syndrome in adolescents, 14 dyslipidemia in children 15 and hypertension in adults. 16 In addition, a recent ecological study that included data from 19 European countries showed a positive association between household availability of ultra-processed foods and the prevalence of obesity among adults.…”
Section: Introductionmentioning
confidence: 99%
“…These foods present an unbalanced nutritional composition, lack micronutrients and phytochemicals, contain low levels of fiber and protein and are rich in free sugars, total fats, saturated and trans fats and sodium. 8 Previous studies have identified positive associations between consumption of ultra-processed foods and obesity, [9][10][11][12][13] metabolic syndrome in adolescents, 14 dyslipidemia in children 15 and hypertension in adults. 16 In addition, a recent ecological study that included data from 19 European countries showed a positive association between household availability of ultra-processed foods and the prevalence of obesity among adults.…”
Section: Introductionmentioning
confidence: 99%
“…Additional factors that were absent from the frameworks and for which evidence exist were added (e.g. high-sugar, nutrient-poor foods, ultra-processed foods (17)(18)(19)(20)(21)(22)(23) , food environment (24,25) , supermarket growth (26) , street vendors, food eaten away from home (27,28) , literacy (29) , urban residency (30) , microbiome (31,32) ). The final list of shared drivers was reviewed by the authors and drivers for which consensus was reached that they are shared were maintained, and in some cases, the terminologies were harmonised.…”
Section: Identifying and Categorising The Shared Drivers Of The Doublmentioning
confidence: 99%
“…People spend most of their lives in the postprandial state since the true fasting state occurs only in the last 2 h of a regular night sleep (51) ; therefore, quality of food consumed will be key in the effect on health. Currently most of the foods consumed frequently are ultra-processed products (52,53) , which are mainly foods of poor quality (e.g. higher in CH of elevated GI and GL as well as low in dietary fibre and energy dense) (54) .…”
Section: Discussionmentioning
confidence: 99%